Have Chinese firms become smaller? If so, why? - Yang, Qiming; Zhang, Xiaobo; Zhu, Wu (International Food Policy Research Institute, 2016)
Normally as an economy develops, firm sizes increase. However, as measured by the employment rate, the firm size in China declined from 2004 to 2008. In this paper, we develop a structural dynamic model with heterogeneous workers to study the relative contributions of three factors to declining firm size: rising real wages, implementation of minimum wages, and the introduction of a new national labor contract law. While rising wages make a sizeable contribution, we find that the new labor law plays a dominant role in solving the puzzle. In comparison, the impact of minimum wages is more muted.